Respuesta :
first, rearrange the equation to standard line format
3x + 9y = 7
9y = -3x + 7
y = -3/9x + 7/9
y = -1/3x + 7/9
now we know the slope of the line (both the existing and the new parallel one, since they both have the same slope)
y = -1/3x + b
plug in the new point in and solve for b
4 = -1/3(6) + b
4 = -2 + b
b = 6
y = -1/3x + 6 is the equation for the parallel line
3x + 9y = 7
9y = -3x + 7
y = -3/9x + 7/9
y = -1/3x + 7/9
now we know the slope of the line (both the existing and the new parallel one, since they both have the same slope)
y = -1/3x + b
plug in the new point in and solve for b
4 = -1/3(6) + b
4 = -2 + b
b = 6
y = -1/3x + 6 is the equation for the parallel line
Answer:
y = -1/3x + 6 is the equation for the parallel line
Step-by-step explanation:
!!!Just took the test and got a 100%!!!!